2008
DOI: 10.1111/j.1462-2920.2008.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of ribosomal DNA‐containing bacterioplankton genome fragments from a 4000 m vertical profile in the North Pacific Subtropical Gyre

Abstract: High-throughput identification of rRNA gene-containing clones in large insert metagenomic libraries is difficult, because of the high background of host ribosomal RNA (rRNA) and rRNA genes. To address this challenge, a membrane hybridization method was developed to identify all bacterial small subunit rRNA-containing fosmid clones of microbial community DNA from seven different depths in the North Pacific Subtropical Gyre. Out of 101,376 clones screened, 751 rDNA-containing clones were identified that grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 64 publications
12
105
0
Order By: Relevance
“…The Deltaproteobacteria were dominated by the SAR324 cluster , another typical deep water cluster earlier reported from the Arctic (Bano and Hollibaugh, 2002) but also from the Antarctic (Lopez-Garcia et al, 2001) and North Atlantic (Gonzalez et al, 2000). The SAR406 cluster, previously detected in various oceanic provinces (Gordon and Giovannoni, 1996;Gallagher et al, 2004;Pham et al, 2008), as well as the Chloroflexi SAR202 cluster , described as abundant and ubiquitous in meso-and bathypelagic waters Bano and Hollibaugh, 2002;Morris et al, 2004;Varela et al, 2008a), were other abundant clusters of the dark ocean.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The Deltaproteobacteria were dominated by the SAR324 cluster , another typical deep water cluster earlier reported from the Arctic (Bano and Hollibaugh, 2002) but also from the Antarctic (Lopez-Garcia et al, 2001) and North Atlantic (Gonzalez et al, 2000). The SAR406 cluster, previously detected in various oceanic provinces (Gordon and Giovannoni, 1996;Gallagher et al, 2004;Pham et al, 2008), as well as the Chloroflexi SAR202 cluster , described as abundant and ubiquitous in meso-and bathypelagic waters Bano and Hollibaugh, 2002;Morris et al, 2004;Varela et al, 2008a), were other abundant clusters of the dark ocean.…”
Section: Discussionmentioning
confidence: 84%
“…Although microbes have an essential role in ecosystem functioning, very little is known about the factors structuring marine community distribution. Microbial communities have been described as stratified with depth Field et al, 1997;Karner et al, 2001), and depth has until recently been considered as the main factor explaining differences in marine microbial community composition (DeLong et al, 2006;Pham et al, 2008). Light availability (irradiance) is thought to be the main abiotic factor structuring communities in the euphotic zone (Giovannoni and Stingl, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Consistiales (predominantly Pelagibacter) recruited B13-35% of the total classified 16S rRNA gene reads from all depths, supporting the high abundance of Pelagibacter populations throughout the water column (Eiler et al, 2009) and their under-representation in large-insert metagenomic libraries, at least for the populations residing shallower depths (Pham et al, 2008;Temperton et al, 2009). The other major groups included Prochlorales in the photic zone (B17-51%), Cenarchaeales (B22%) and the uncultured deltaproteobacterial group SVA0853 (B9%) at 500 m, and Acidimicrobidae (B2-8%) at all depths.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported an apparent underrepresentation of the SAR11 cluster of the Alphaproteobacteria in BAC and fosmid libraries (Pham et al, 2008;Feingersch and Béjà, 2009;Temperton et al, 2009). Temperton et al (2009) proposed that the low GC content of Candidatus Pelagibacter rendered its DNA more susceptible to fracturing, thereby biasing its inclusion in libraries requiring large insert sizes.…”
Section: Introductionmentioning
confidence: 99%